Home Industry Assistance Upgrades Sambel Pecel Mbak Nur’s Production Capacity and Product Quality - Dwi Ishartani; Setyaningrum Ariviani; Siswanti Siswanti; Gusti Fauza; Dimas Rahadian Aji Muhammad; Windi Atmaka (PRIMA: Journal of Community Empowering and Services, 2025)
Sambel pecel home industry, founded by Tri Nurhayati, sells sambel pecel (pecel sauce) products under the brand “Sambel Pecel Mbak Nur". As a newcomer, “Sambel Pecel Mbak Nur" already had quite a lot of enthusiasts. However, the production capacity had only reached 20 kgs/month due to constraints on the equipment. “Sambel Pecel Mbak Nur” had only a small capacity of the chopper, so the production process ran inefficiently. Excess oil of the product is also a problem, causing shorter product shelf life. Another problem was less attractive packaging and labelling, as it only used thin, clear, flat polypropylene plastic bags as primary packaging and thin, clear, flat polyethylene plastic as secondary packaging, with limited information on the label. The last problem faced was the limited demand and market reach. The aims of this program were to increase the production capacity of sambel pecel, improve product quality, improve product packaging and labelling, increase the number of sales, and expand marketing reach. This community service activity has introduced appropriate technology at the home industry “Sambel Pecel Mbak Nur" by introducing a larger capacity chopper and a spinner to drain excess oil. This activity has also improved the product packaging by introducing thick standing pouches, plastic, and thicker mica plastic as secondary packaging with a more informative label, so that the product is better protected and more attractive. Increased market reach has been attempted with digital marketing training. From the evaluation conducted, it can be seen that the introduction of appropriate technology and training in e-marketing was able to upgrade production capacity and product quality of “Sambel Pecel Mbak Nur".